2016
DOI: 10.1289/ehp.1509838
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Exposure to Ambient Air Pollutants and the Onset of Asthma: An Administrative Cohort Study in Québec

Abstract: Background:Although it is well established that air pollutants can exacerbate asthma, the link with new asthma onset in children is less clear.Objective:We assessed the association between the onset of childhood asthma with both time of birth and time-varying exposures to outdoor air pollutants.Method:An open cohort of children born in the province of Québec, Canada, was created using linked medical–administrative databases. New cases of asthma were defined as one hospital discharge with a diagnosis of asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 35 publications
4
77
1
1
Order By: Relevance
“…Figure 1 shows the flow of papers. A total of 42 studies met our inclusion criteria [31,32,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,50,51,52,58,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flow of papers. A total of 42 studies met our inclusion criteria [31,32,33,34,36,37,38,39,40,41,42,43,44,45,46,47,48,50,51,52,58,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Ages of participants ranged from 1 to 18 years old and sample sizes ranged from 184 [69] to 1,133,938 [85]. Follow-up periods ranged from 1 to 16 years [47].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple population studies have shown an association between exposure to air pollutants and increased risk of asthma (8992). An increased risk of developing asthma associated with self-reported or assumed “low-level or moderate irritant exposures” has also been suggested from epidemiologic studies, and has been listed as possible IIA in the European Academy of Allergy and Clinical Immunology Task Force statement on IIA (4), with examples given as work as cleaners or work with pesticides, and in the wood industry.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of epidemiological studies have linked exposure to PM with a variety of adverse health effects including respiratory and cardiovascular diseases, and mortality [1][2][3]. Children are particularly susceptible; exposure to PM 2.5 (PM with aerodynamic diameter ≤2.5 µm) early in life can lead to the onset of asthma [4], wheeze [5], and decreased lung function [6].…”
Section: Introductionmentioning
confidence: 99%